2020
DOI: 10.1371/journal.pone.0243447
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio predicts early mortality in females with metastatic triple-negative breast cancer

Abstract: Background The aim of this study was to determine the utility of the neutrophil-to-lymphocyte ratio (NLR) as a biomarker for predicting early-mortality (<2 years) among females with metastatic triple-negative breast cancer (mTNBC). Methods We reviewed 118 medical records of females with mTNBC. The cut-off value for the NLR (<2.5 and ≥2.5) was determined with receiver operating characteristic curves (area under the curve: 0.73; 95% CI: 0.62–0.85). Survival curves were estimated using the Kaplan-Meier me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…( 25 ) reported an association between high NLR and worse OS in 2,374 eBC and mBC patients, for patients with luminal subtypes. In another study concerning mTNBC, NLR> 2.5 at diagnosis was a useful predictor of poor OS, regardless of the subsequent treatment ( 26 ). In HR+/HER2- eBC, high NLR (>2.25) after neoadjuvant chemotherapy was correlated with poorer disease free survival (DFS) and OS, especially in patients with non-pathologic complete response (pCR) ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 25 ) reported an association between high NLR and worse OS in 2,374 eBC and mBC patients, for patients with luminal subtypes. In another study concerning mTNBC, NLR> 2.5 at diagnosis was a useful predictor of poor OS, regardless of the subsequent treatment ( 26 ). In HR+/HER2- eBC, high NLR (>2.25) after neoadjuvant chemotherapy was correlated with poorer disease free survival (DFS) and OS, especially in patients with non-pathologic complete response (pCR) ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Association of NLR is calculated with outlined clinic-pathological features of breast cancer by using the chi-square test and the P-value of less than 0.05 is considered significant. The cut-off value for the NLR ratio is 2.5 as quoted by other authors [14,15] Univariate logistics regression was applied for variables found significant by the chisquare test.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying risk factors for postoperative recurrence, metastasis, or death in ovarian cancer patients is beneficial for improving treatment measures to prolong the survival and predict the prognosis of these patients. In recent years, the relationship between the neutrophil-to-lymphocyte ratio (NLR) and malignant tumors has gradually attracted increasing attention from scholars, and studies have confirmed that NLR can predict patient prognosis in breast, liver, lung, and bladder cancers, these studies showed that a higher level of NLR was associated with a poor prognosis (5)(6)(7)(8). Studies have also shown that NLR is associated with the efficacy of neoadjuvant chemotherapy in patients with ovarian cancer, a higher level of NLR is associated with a poor efficacy of neoadjuvant chemotherapy (9,10), but whether this change in efficacy translates into a long-term mortality benefit is unclear.…”
Section: Introductionmentioning
confidence: 99%